Factors related to adherence to drug treatment in public university workers - Lucas Pinto de Lima; Priscila Fernanda de Almeida; Cristina Berger Fadel; Luciane Patrícia Andreani Cabral; Everson Augusto Krum; Danielle Bordin (Universidade Federal do Ceará, 2021)
Objective: to analyze factors associated with medication adherence among public university workers who reported use of continuous medication. Methods: cross-sectional study carried out with 629 workers from a public university. Data were collected through interviews using forms adapted from the Brazilian Ministry of Health and analyzed using the chi-square test. Results: three hundred thirty-one (52.6%) participants were users of continuous medication, of these, 175 (52.9%) had a partially satisfactory adherence pattern and 156 (47.1%) a totally satisfactory pattern. Workers with chronic back problems, depression, weakness/tiredness, dyspnea, and chest pain had significantly less adherence to drug treatment (p≤0.050). Sociodemographic and labor characteristics, polypharmacy, and type of medication were not associated with medication adherence (p>0.050). Conclusion: satisfactory drug adherence was observed among the participants in relation to drug treatment, and the presence of some symptoms and specific chronic diseases was associated with partially satisfactory drug adherence.